Growth of white shrimp post-larvae immersed in recombinant fish growth hormone - Dita Puji Laksana; Siti Subaidah; Muhammad Zairin Junior; , Alimuddin; Odang Carman (Jurnal Akuakultur Indonesia)
ABSTRACT